Anesthetic Management and Bispectral Index in a Child with Miller-Dieker Syndrome: A Case Report - Sang Jin Park; Jongyoon Baek; Suyoun Chun; Eun Kyung Choi (MDPI AG, 2023)
Miller-Dieker syndrome (MDS) is a genetic disorder characterized by classic lissencephaly, distinctive facial features, intellectual disability, seizures, and early death. The anesthetic management of patients with MDS should focus on airway manipulation with the risk of potentially difficult intubation, seizure control due to lissencephaly, and any other clinical complications. Herein, we report a case of anesthetic management in a child with MDS and describe relevant clinical features in a perioperative anesthetic setting. This case highlights the importance of difficult airway manipulation using a videolaryngoscope, seizure management with regard to anesthetics use, and the low validity of BIS monitoring in patients with MDS.